The Effect of Smarca2 Expression on Tumor Mass Expansion, Lymph Node Enlargement, and Histopathological Type of Nasopharyngeal Carcinoma - Lubis, Ika Syani Putri (LPPM Universitas Mohammad Husni Thamrin, 2025)
Nasopharyngeal carcinoma (NPC) is a malignant disease of the nasopharyngeal epithelium. This malignancy is often found in the Rosenmüller fossa. This tumor can spread to various areas and organs of this structure, including the nasal cavity, skull base, parapharyngeal space, and oropharynx. Diet, oncovirus infection, Epstein-Barr virus (EBV), and genetic alterations are some of the causes of NPC development. SMARCA2 is considered a tumor suppressor. To date, very few studies have comprehensively studied the mechanism of SMARCA2 inactivation. Multi-omics analysis was used to study the mechanism of SMARCA2 inactivation in The Cancer Genome Atlas (TCGA) database, and the dCas9-DNMT3a system was used to assess the role of promoter methylation in regulating SMARCA2 transcription. Decreased SMARCA2 expression was significantly associated with SMARCA2 promoter hypermethylation. This study aims to examine the influence of Smarca2 expression on tumor mass expansion, lymph node enlargement, and histopathological type of nasopharyngeal carcinoma. This study used a cross-sectional analytical study design by collecting secondary data from medical records of nasopharyngeal carcinoma patients. The results showed that tumor expansion in NPC patients was generally T3 and T4, with a total of 17 people (68%). Enlarged lymph nodes in the neck most often occurred in N2 and N3, with a total of 21 people (84%). The majority of patients were also in clinical stages III and IV as many as 23 people (92%).